2010
DOI: 10.1159/000313940
|View full text |Cite
|
Sign up to set email alerts
|

Different Immunosuppressive Combinations on T-Cell Regulation in Renal Transplant Recipients

Abstract: Background/Aims: Recent studies indicate that regulatory T-cells (Tregs) promote transplant tolerance. We studied Treg levels in 39 stable renal transplant recipients to determine the sizes of the Treg populations and the effects of treatment regimens thereof. Methods: All patients (19 with good graft function and 20 with chronic allograft nephropathy) received induction therapy (basiliximab) and were on triple immunosuppressive regimens with calcineurin inhibitors (cyclosporine or tacrolimus), mycophenolate m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 55 publications
4
27
0
Order By: Relevance
“…In liver transplant recipients, conversion from CNI to MMF with a 1-time dose of daclizumab showed an increase in the percentage of Treg from baseline 114 . Analysis of kidney transplant patients on stable immunosuppression regimens identified higher levels of CD4 + CD25 high FOXP3 + Treg in patients receiving MMF versus everolimus 115 . Overall, preclinical and clinical evidence thus far suggest that MMF is compatible with Treg homeostasis and function.…”
Section: Impact Of Approved Immunosuppressive Drugs On Tregmentioning
confidence: 98%
“…In liver transplant recipients, conversion from CNI to MMF with a 1-time dose of daclizumab showed an increase in the percentage of Treg from baseline 114 . Analysis of kidney transplant patients on stable immunosuppression regimens identified higher levels of CD4 + CD25 high FOXP3 + Treg in patients receiving MMF versus everolimus 115 . Overall, preclinical and clinical evidence thus far suggest that MMF is compatible with Treg homeostasis and function.…”
Section: Impact Of Approved Immunosuppressive Drugs On Tregmentioning
confidence: 98%
“…Previous reports have described how CNIs reduce regulatory T cells (Tregs) but increase IL-17-producing T helper cells (Th17) despite reducing the overall number of T cells. 512 The loss of Tregs, which secrete the anti-inflammatory cytokines TGFbeta and IL-10, kill pro-inflammatory immune cells, and promote immune tolerance, and the augmentation of Th17 cells that produce the potent pro-inflammatory and pro-hypertensive cytokine IL-17, together lead to organ dysfunction and hypertension. 8, 9 However, it is unknown whether targeting these effects can have vascular and renal protective effects and attenuate the hypertension caused by CNIs.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Conversely, corticosteroids have been reported to increase Treg frequency and FOXP3 expression in patients with autoimmune diseases. 13,14 Finally, renal transplant recipients receiving MMF show significantly higher CD4…”
Section: Introductionmentioning
confidence: 99%
“…12 Furthermore, studies on liver transplant patients with renal impairment on CsA and converted to MMF showed that the new treatment may reverse the negative effect of calcineurin inhibitors on Tregs. 15 This study has focused on the consequences of using drugs commonly applied in the treatment of transplant patients, namely TAC, MPA and mPr, for the viability, function and stability of ex vivo expanded Tregs.…”
Section: Introductionmentioning
confidence: 99%